GLOW IN THE DARK MEDIAN FRONTAGE AND PEDESTRIAN AS A GUIDE FOR DRIVERS AT NIGHT - Amar Mufhidin; Salma Ayu Rahmanita; Rizalludin, Rizalludin; Asiyah, Tintin; Laelasari, Laelasari (Jurnal Pensil : Pendidikan Teknik Sipil, 2024)
The condition of the road plays a significant role in the driving experience and traffic safety. However, excessive use of Street Lighting (LPJU) can have an impact on global warming. This research utilizes a Research and Development (R&D) approach to develop phosphorescent paint technology for curbstones. The main goal of this research is to create a solution that aids the visualization of drivers and pedestrians in dark road conditions. Additionally, the research aims to reduce excessive electricity consumption, which is a crucial step in supporting efforts to mitigate global climate change. The research results show that the application of phosphorescent paint on curbstones can enhance visibility at night and provide clear visual guidance for road users. This technology also successfully reduces reliance on external street lighting, resulting in significant electricity savings. Thus, this research makes a positive contribution to improving traffic safety and supporting energy conservation efforts to protect the environment.